THE LEGAL STATUS OF AGRICULTURAL ADVISORY SERVICES IN THE EUROPEAN UNION AND THE REPUBLIC OF SERBIA: A COMPARATIVE ANALYSIS - Maksimovic Sekulic, Nina; Lečić , Boriša; Madunić, Ljubomir (Economics of Agriculture, 2026)
Farm Advisory System (FAS) in the European Union areundergoing significant legal and institutional transformationin response to climate change, digitalization, and theevolving objectives of the Common Agricultural Policy(CAP). This paper analyses the changing legal positionof advisory services within the Agricultural Knowledgeand Innovation System (AKIS), with particular emphasison Regulation (EU) 2021/2115. The study appliesa comparative and qualitative approach to examinedifferences between advanced European Union models andthe current regulatory framework of the Republic of Serbia.The findings indicate that Serbian legislation remainspredominantly based on a traditional model of knowledgetransfer and lacks sufficient digital and institutionalintegration. The paper argues that harmonization withEuropean Union standards must extend beyond formallegal alignment and include the strengthening of advisorycapacities, digital governance, and innovation-orientedsupport mechanisms. Such reforms are essential for theeffective implementation of IPARD III and the sustainabledevelopment of rural communities.